Assessment of Awareness and outlook of a Pathological Autopsy among Medical Students - Varsha Pande; Bharat Umakant Patil; Raju Wamanrao Gore; Swapnil Patond (Institute of Medico-legal Publications Pvt Ltd, 2021)
Aim: This study assesses the awareness, outlook & knowledge toward Pathological autopsy amongstmedical students at tertiary care teaching center.Objectives: To assess medical student’s opinions, feelings and attitude towards autopsy and its importancein medical education.Material and Method: We conducted a study of 300 students studying 3rd and 5th semesters where theytaught about the subject. We used questionnaire containing questions relating to autopsy to assess theawareness, outlook & knowledge towardPathological Autopsy.Results: Amongst the class of 300 students no statistically difference is observed in the views of male andfemale students on any item in the present study.Conclusion: The Forensic Medicine is important subject for medical profession. Teaching how to perform anautopsy is relevant and plays a positive role in medical education, and autopsy training from both theoreticaland practical perspectives must be included in the forensic medicine curriculum. Medical institutes musttake responsibility to increase awareness about the effect of media on medical education.